The Design of IMF-Supported Programs - Christofides, Charalambos (Occasional Papers; Occasional Paper, 2005)
This collection of papers examines IMF-supported programs over the period 1995-2000 in both middle-income and low-income countries. In order to seek insights from a comparison across different types of programs, the sections entitled"Objectives and Outcomes," "Policy Formulation and Analytical Frameworks," and "Macroeconomic and Structural Policies" address a number of questions regarding the economic programs for which national authorities seek the IMF's financial support: the specific goals of IMF-supported programs, and the challenges they face; how programs are formulated; the components of programs; and how program success should be judged.